Meningkatkan Kemampuan Guru Dalam Melaksanakan Penelitian Tindakan Kelas Melalui Teknik Workshop di SDN 7 Telaga Biru dan SDN 9 Telaga Biru Kabupaten Gorontalo - Imran Tululi (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
The problem examined in this study is whether the ability of teachers to carry out classroom actionresearch in the 7 primary schools of Telaga Biru and the 9 primary schools in Telaga Biru GorontaloRegency can be improved through workshop techniques? "This study aims to improve the ability ofteachers to carry out classroom action research through workshop techniques in the 7 primaryschools in Telaga Biru and 9 primary schools in Telaga Biru, Gorontalo District. The method used inthis research is descriptive method. The results showed that, 1) the ability of teachers to carry outclassroom action research in public elementary schools 7 Telaga Biru and in public elementaryschools 9 Telaga Biru had increased after being subjected to action through II cycles, 2) an increasein the teacher's ability to carry out classroom action research was marked with the optimal mastery ofthe 10 indicators of classroom action research namely a) the ability to identify problems, b) the abilityto formulate problems, c) the ability to formulate hypotheses, d) the ability to make researchinstruments, e) the ability to make plans for action and monitoring, f) the ability to implement actionsand observing them, g) the ability to collaborate with partner teachers in research, h) the ability toprocess and interpret data, i) the ability to make conclusions of research results, and j) the ability tocompile reports on research results.